Subscribe to our Youtube Channel - https://you.tube/teachoo

Last updated at Dec. 8, 2016 by Teachoo

Transcript

Ex 3.3, 14 Prove that sin 2x + 2sin 4x + sin 6x = 4cos2 x sin 4x Taking L.H.S. sin 2x + 2sin 4x + sin 6x = (sin 6x + sin 2x) + 2sin 4x = 2 sin ((6 + 2 )/2) cos ((6 2 )/2) + 2sin 4x = 2 sin (8 /2) cos (4 /2) + 2sin 4x = 2 sin 4x cos 2x + 2sin 4x = 2 sin 4x (cos 2x + 1) = 2 sin 4x ( 2cos2x 1 + 1) = 2 sin 4x (2cos2x) = 4 sin 4x cos2x = R.H.S Hence L.H.S = R.H.S Hence proved

Cos x + cos y formula

Chapter 3 Class 11 Trigonometric Functions

Concept wise

- Radian measure - Conversion
- Arc length
- Finding Value of trignometric functions, given other functions
- Finding Value of trignometric functions, given angle
- (x + y) formula
- 2x 3x formula - Proving
- 2x 3x formula - Finding value
- cos x + cos y formula
- 2 sin x sin y formula
- Finding Principal solutions
- Finding General Solutions
- Sine and Cosine Formula

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.